RAPPORT AND ADDRESS TERMS IN FAMILY GUY CARTOON: Can (Targeted) Audience Identify a Social Dimension of Relationship? - R. Arief Nugroho (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2010)
Brown and Levinson (1978, 1987) and Leech (1983) both offer that power and distance relationship indicated through address terms have an important impact on how the evaluation toward politeness occur in a community context. The occurrences in rapport and address terms emerge two grand research questions: what variants of address terms found in Family Guy cartoon and how is the rapport1realized through address system? The findings of the research show that there are five variants of address terms used in the film: Personal Names, Title Terms, Kin Terms, Honorifics or Terms of Formality, and Terms of Intimacy.Keywords: Address Terms, Rapport, Relationship, Social Dimension